Distribution of airway smooth muscle remodelling in asthma: Relation to airway inflammation. Issue 1 (26th September 2014) - Elliot, John G.; Jones, Robyn L.; Abramson, Michael J.; Green, Francis H.; Mauad, Thais; McKay, Karen O.; Bai, Tony R.; James, Alan L.
Abstract Background and objective Pathological phenotypes of asthma have been based predominantly on inflammation, rather than airway wall remodelling. Differences in the distribution of airway smooth muscle (ASM) remodelling between large and small airways may affect clinical outcomes in asthma. The aim of this study was to examine the distribution of ASM remodelling and its relation to airway inflammation. Methods Post‐mortem cases of asthma (n = 68) were categorized by the distribution of increased thickness of the ASM layer (relative to nonasthmatic controls, n = 37), into 'large only' (LO, n = 15), 'small only' (SO, n = 4) 'large/small' (LS, n = 24) or no increase (NI, n = 25). Subject characteristics, ASM and airway wall dimensions and inflammatory cell numbers were compared between groups. Results Apart from reduced clinical severity of asthma in NI cases (P = 0.002), subject characteristics did not distinguish asthma groups. Compared with control subjects, ASM cell number, reticular basement membrane thickness, airway wall thickness, percent muscle shortening and eosinophil number were increased (P < 0.05) in both large and small airways in LS cases and only the large airways in LO cases. Increased numbers of neutrophils were observed only in the small airways of LO cases. Conclusions Distinct distributions of ASM remodelling are seen in asthma. Pathology limited to the small airways was uncommon. Increased thickness of the ASM layer was associated with airway remodelling and eosinophilia, but not neutrophilia. These data support the presence of distinct pathological phenotypes based on the site of increased ASM.